Dynamic changes in In vitro rumen fermentation, nutrient degradation, and microbial communities of fermentation inoculant-treated licorice stem and leaf silage under different dry matter contents - Limin Tang; Haonan Liu; Qifeng Gao; Yuliang Sun; Xinyu Xu; Wenghao Li; Dong Lu; Yulan Ren; Houjun Yu; Tao Jiang (PLoS ONE, 2026)
This study aimed to explore the effects of semi-dry licorice ( Glycyrrhiza uralensis ) stem and leaf silage on dynamic changes in dairy cow in vitro rumen fermentation parameters, nutrient degradation rates, and microbial community composition. Silage substrates with four dry matter (DM) contents (45%, 50%, 55%, 60%; L45, L50, L55, L60) were prepared by adjusting moisture with additives, with 5 replicates per group per time point. In vitro fermentation lasted 72 h, with cumulative gas production (GP), fermentation parameters, microbial composition, and nutrient degradation rates measured at 0, 3, 12, 24, 72 h. Principal component analysis (PCA) and gray relational analysis (GRA) were used for comprehensive evaluation. Results showed that L55 had significantly higher 72-h GP, microbial crude protein (MCP), and nutrient degradation rates ( P < 0.05), and lower pH at 3 and 72 h ( P < 0.05). It also had higher total volatile fatty acid (TVFA) and acetic acid (AA) at 12, 24 h ( P < 0.05), the highest proportion of unique OTUs at 3, 72 h, and superior α-diversity indices (ACE, Chao1) compared to L45 (P < 0.05). L55 showed dominant early abundances of functional genera (e.g., Prevotella ) and higher metabolic pathway proportions ( P < 0.05 vs. L60), ranking first in PCA and GRA. Conclusion: 55% DM in licorice semi-dry silage optimizes in vitro rumen fermentation and microbial composition, presenting the best feeding value.